2020
DOI: 10.1016/j.ecss.2020.106844
|View full text |Cite
|
Sign up to set email alerts
|

Effective design of managed realignment schemes can reduce coastal flood risks

Abstract: Managed realignment (MR) constitutes a form of nature-based adaptation to coastal hazards, including sea level rise and storm surges. The implementation of MR aims at the (re)creation of intertidal habitats, such as saltmarshes, for mitigating flood and erosion risks and for creating more natural shorelines. However, some evidence suggests that the desired coastal protection function of MR schemes (in terms of high water level (HWL) attenuation) may be limited and it was hypothesized that this was due to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…In a previous study, the model was calibrated and validated against field measurements of the highest spring tides of the year 2017. Root mean square errors between modelled and measured water depths ranged between 0.05 and 0.06 m and mean absolute errors of peak water levels between 0.02 and 0.04 m. Model calibration included a range of Manning's n coefficients for saltmarsh surfaces (0.035-0.09) and revealed that the model was not very sensitive to these variations (Kiesel et al 2020). We note that the effects of bottom friction are also dependent on water depth (Delft Hydraulics 2003;Loder et al 2009;Wamsley et al 2010;Temmerman et al 2012), and the calibration of the model is representative of spring tide conditions.…”
Section: Model Setup and Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, the model was calibrated and validated against field measurements of the highest spring tides of the year 2017. Root mean square errors between modelled and measured water depths ranged between 0.05 and 0.06 m and mean absolute errors of peak water levels between 0.02 and 0.04 m. Model calibration included a range of Manning's n coefficients for saltmarsh surfaces (0.035-0.09) and revealed that the model was not very sensitive to these variations (Kiesel et al 2020). We note that the effects of bottom friction are also dependent on water depth (Delft Hydraulics 2003;Loder et al 2009;Wamsley et al 2010;Temmerman et al 2012), and the calibration of the model is representative of spring tide conditions.…”
Section: Model Setup and Data Processingmentioning
confidence: 99%
“…Results from studies based on hydrodynamic modelling suggest that the coastal protection function of MR schemes can be improved by applying a scheme design (i.e. configuration of breaches and dikes) that aims at keeping internal water depths low, but attenuation rates > 10 cm km −1 are only achieved by establishing vast and wide shallow water areas (Kiesel et al 2020). Problematically, MR sites are typically smaller than Freiston Shore (66 ha).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, systems where the first dike is already breached before a storm are classified as a type V system. While the first dike can no longer prevent flooding by itself, it can still aid in reducing water levels at the second dike, as was studied for the Freiston Shore Managed Realigment site (UK) (Kiesel et al, 2020).…”
Section: Hinterlandmentioning
confidence: 99%
“…Water is not retained by the first dike and only wave and water level attenuation effects can be expected in these systems. Rather than an erosionovertopping model used in this study, a hydrodynamic wave and flow model is needed to assess the loads propagating towards the second dike in these systems (Kiesel et al, 2020). These examples show that the selection of models needed in the transmission step of the framework greatly depends on the type of system and its context.…”
Section: Comparison With Other Double Dike Systemsmentioning
confidence: 99%